Everyday life in the segmented city - Perrone, Camilla; Manella, Gabriele; Tripodi, Lorenzo (Bingley, U.K. : Emerald, 2011)
This volume of Research in Urban Sociology is composed of a selection of the papers presented at the conference 'Everyday Life in the Segmented City' held in July 2010, Florence. The conference gathered a multiplicity of approaches and points of view dealing with issues of global urbanization. Urbanization is a phenomenon inscribed into the globalization process that has enormous consequences in the transformation of urban space and the everyday life of citizens, and is reflected also in the flourishing of an analytical discourse increasingly transcending the boundaries of established urban disciplines. The progressive extension of the urban domain beyond the limits of the city and across diverse scales has its corollary in the progressive segmentation of the urban dimension along multiple lines of physical, social, economic, cultural and ethnic nature. This volume focuses on the perspective of the everyday to analyze how practices and policy can overcome the spin towards fragmentation and anomie, and reinforce social cohesion for a more just and livable city, endorsing the 'right to the city' as presented by the seminal work of Henri Lefebvre.
Everyday life in the segmented city : an introduction / Lorenzo Tripodi -- ch. 1. What would a 'D / Camilla Perrone -- ch. 2. From urban sprawl to sustainable cities : a neighborhood perspective in urban studies / Marco Castrignanò, Gabriele Manella -- ch. 3. The productive gaze : Florence as archetype of the cinematic city / Lorenzo Tripodi -- ch. 4. The politics of space in an ethno-nationally contested city : strategies and everyday practices / Rachel Kallus -- ch. 5. This is what radical democracy looks like! : reclaiming urban space in Vienna / Julia Edthofer -- ch. 6. The segmented quotidian made visible : Jean vigo's a propos de Nice / Micah Trippe -- ch. 7. Segmented cities with fuzzy walls : changes in informal settlements as seen through a multiscale analysis / Mauro Normando Macêdo Barros Filho, Circe Maria Gama Monteiro -- ch. 8. Global phenomenon, local effect : the question of place identity in view of the globalization and commercialization of urban space / Magdalena Zmudzinska-Nowak -- ch. 9. A heritage claim to public space : examples from a mixed neighbourhood in Drammen, Norway / Grete Swensen, Sveinung Krokann Berg, Johanne Sognnæs -- ch. 10. Sensitive urban renewal or gentrification? : the case of the Karmeliterviertel in Vienna / Florian J. Huber -- ch. 11. Users' perception and representative image of the 'Navigli' area in Milan / Stefano Forbici, Davide Diamantini -- ch. 12. Youth policies, social sanitation, and contested suburban nightscapes / Jordi Nofre -- ch. 13. Social change and social capital in an English suburban council estate : the Whitley Estate, reading, in South East England / Mark Clapson -- ch. 14. Active citizenship in Italian cohousing : a preliminary reflection / Chiara Durante.
Print version record
Keywords: Social Science -- Sociology -- Urban; Social Science -- Sociology -- General; Social Science -- General; Sociology; Urban communities; Sociology, Urban